Study protocol for yoga-based lifestyle intervention for healthy ageing phenotype in the older adults (yHAP): a two-armed, waitlist randomised controlled trial with multiple primary outcomes - Amit Singh; Vijaya Majumdar; Atmakur Snigdha; N K Manjunath; Raghuram Nagarathna; Ramesh Mavathur; Kalpana S R; Nagendra H R (BMJ Open)
Introduction The conceptualisation of healthy ageing phenotype (HAP) and the availability of a tentative panel for HAP biomarkers raise the need to test the efficacy of potential interventions to promote health in older adults. This study protocol reports the methodology for a 24-week programme to explore the holistic influence of the yoga-based intervention on the (bio)markers of HAP.Methods and analysis The study is a two-armed, randomised waitlist controlled trial with blinded outcome assessors and multiple primary outcomes. We aim to recruit 250 subjects, aged 60–80 years from the residential communities and old age clubs in Bangalore city, India, who will undergo randomisation into intervention or control arms (1:1). The intervention will include a yoga-based programme tailored for the older adults, 1 hour per day for 6 days a week, spread for 24 weeks. Data would be collected at the baseline and post-intervention, the 24th week. The multiple primary outcomes of the study are the (bio)markers of HAP: glycated haemoglobin, low-density lipoprotein cholesterol (LDL-C), systolic blood pressure, and forced expiratory volume in 1 s for physiological and metabolic health; Digit Symbol Substitution Test, Trail Making Tests A and B for cognition; hand grip strength and gait speed for physical capability; loneliness for social well-being and WHO Quality of Life Instrument-Short Form for quality of life. The secondary outcomes include inflammatory markers, tumour necrosis factor-alpha receptor II, C reactive protein, interleukin 6 and serum Klotho levels. Analyses will be by intention-to-treat and the holistic impact of yoga on HAP will be assessed using global statistical test.Ethics and dissemination The study is approved by the Institutional Ethics Committee of Swami Vivekananda Yoga Anusandhana Samsthana University, Bangalore (ID: RES/IEC-SVYASA/143/2019). Written informed consent will be obtained from each participant prior to inclusion. Results will be available through research articles and conferences.Trial registration number CTRI/2021/02/031373.